A rare case of primary disseminated multi-drug resistant tuberculosis - Vinod, Sushmita; Gururaj, Prasanth; Vadivelu, Gangadharan (International Journal of Advances in Medicine, 2022)
Tuberculosis (TB) is the commonest cause of infection-related death globally. Disseminated tuberculosis (TB) is a life-threatening disease which results from the hematogenous spread of Mycobacterium tuberculosis. Genitourinary tuberculosis (GUTB) is usually caused as a result of the hematogenous spread of the mycobacteria during the initial infection. The patient’s clinical presentation may vary from asymptomatic to non-specific symptoms related to the organ involved and may also overlap with urinary tract infections caused by other pathogens hence delaying the diagnosis. Here we report one such case where the vague symptoms of the patient and absence of respiratory symptoms delayed the diagnosis of primary disseminated multi-drug resistant (MDR) tuberculosis.